2021
DOI: 10.3389/fcell.2021.636037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin Inhibitors in Renal Cell Carcinoma: Potential, Limitations, and Perspectives

Abstract: Several elements highlight the importance of the mechanistic target of rapamycin (mTOR) in the biology of renal cell carcinoma (RCC). mTOR signaling pathway is indeed frequently activated in RCC, inducing cancer cell proliferation and survival. In addition, mTOR promotes tumor angiogenesis and regulates the expression of hypoxia-inducible factors that play an important role in a subset of RCC. Despite mTOR protumorigenic effects, mTOR inhibitors have failed to provide long-lasting anticancer benefits in RCC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 83 publications
1
19
0
1
Order By: Relevance
“…Nowadays, our efforts have largely improved the management of ccRCC patients. Apart from surgical resection, molecular targeted drugs, including drugs targeting VEGF, PDGFR, EGFR, and mTOR, are available for patients with high recurrence risk and for patients lacking opportunity for radical resection [47,48]. However, the therapeutic effects are still not very satisfying and there is no doubt that ccRCC is a In this study, we are mainly focused on IL20RB, whose role in ccRCC is still unknown but has shown its potential as a novel biomarker in some human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, our efforts have largely improved the management of ccRCC patients. Apart from surgical resection, molecular targeted drugs, including drugs targeting VEGF, PDGFR, EGFR, and mTOR, are available for patients with high recurrence risk and for patients lacking opportunity for radical resection [47,48]. However, the therapeutic effects are still not very satisfying and there is no doubt that ccRCC is a In this study, we are mainly focused on IL20RB, whose role in ccRCC is still unknown but has shown its potential as a novel biomarker in some human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MTOR activation occurs frequently in cancers and targeting MTOR using RAD001 has been extensively tested in clinical trials, revealing RAD001 is safe, tolerable and has efficacy at blocking tumor growth in patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed the FDA-approved MTOR inhibitor, RAD001, could be used to block MDR1 activity overcoming MDR1-mediated drug resistance in cancer cells. MTOR activation occurs frequently in cancers and targeting MTOR using RAD001 has been extensively tested in clinical trials, revealing RAD001 is safe, tolerable and has efficacy at blocking tumor growth in patients ( 44 ). RAD001 is currently used to treat several cancers, including renal cell carcinomas (RCC) (NCT00831480), which exhibits frequent overexpression of MDR1 ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the immunosuppressant effect of rapamycin has been observed in several case studies, with transplanted patients reducing the incidence of cancer [118]. In ongoing clinical studies in prostate cancer in which the PI3K/Akt/mTOR pathway is highly expressed, it was observed that rapamycin and its derivatives were well tolerated in prostate cancer patients and decreased mTOR level [119]. In addition to the antiproliferative effect, RAD001 is also used as an immunosuppressant for the treatment of several malignancies in phase I study [120].…”
Section: Phosphoinositide 3-kinase (Pi3k) Pathway Inhibitorsmentioning
confidence: 98%